Merayakan Anekarasa: Membangun Multikulturalisme melalui Pembelajaran Sejarah Kuliner di Kota Medan - Tanjung, Septiansyah; Wawan Darmawan (Jurnal Pendidikan Sejarah, 2022)
The writing of this paper derives from multicultural life in Indonesia, especially Medan, and how to develop the values of multiculturalism among students through history learning. The concept of multicultural education in history learning is then integrated by elaborating local historical studies in the form of culinary development from students’ surroundings. The method used in writing this paper is by developing conceptual ideas through the analysis of literary sources and also oral sources using the historical method. Historical learning that applies multicultural education as a learning goal to instill the values of multiculturalism needs to develop content based on curriculum documents. Core Competencies and Basic Competencies in Indonesian History lessons are the main subjects developed for the aspects of local historical events. This learning management should pay attention to well-formulated planning, organizing, implementation, and evaluation so that the learning objectives can be achieved. The values of multiculturalism formed in students such as recognition, appreciation, and respect, and also learning different cultures through the learning process is believed to be a social capital that can create a harmonization in Indonesia with Bhinneka Tunggal Ika.